Association of self-reported mother–infant relationship with child and adolescent mental health. Issue 2 (20th March 2023) - Rasmussen, Ida Scheel; Wilson, Philip; Overbeck, Gritt; Strandberg-Larsen, Katrine
Abstract : Background: The quality of the relationship between mother and infant may have profound implications for the development of a child. Early indicators of psychological vulnerability may allow targeting of support for the child's cognitive, emotional and social development. A challenging mother–infant relationship could be one indicator of risk. Aims: This study examined variations in psychological well-being and psychopathology among boys and girls according to early maternal perception of the mother–infant relationship. Method: This study is based on 64 663 mother–infant pairs from the Danish National Birth Cohort, for which data on the mother–infant relationship were collected at 6 months postpartum. Behavioural problems were assessed with the Danish version of the Strengths and Difficulties Questionnaire (SDQ) at child ages 7, 11 and 18 years, and we retrieved information on diagnosed childhood and adolescent psychiatric disorders and prescriptions of psychotropic drugs from Danish registries. Results: Children in the challenging mother–infant relationship group had higher odds of behavioural problems at age 7 among both boys and girls. The same pattern of elevated estimates was identified for boys across all SDQ domains and for girls in three of five SDQ domains. All associations were attenuated at age 18, but increased odds of behavioural problems still existed. A challenging early mother–infant relationship increased the offspring's risk of being diagnosed with a psychiatric disorder or being prescribed a psychotropic drug before the age of 18. Conclusion: A challenging self-reported mother–infant relationship was associated with later psychopathological difficulties. Routine clinical enquiry may be useful in identification of future vulnerability.